Peran Rasio Trombosit Limfosit dalam Memprediksi Tingkat Keparahan Pasien Covid-19 - Tania; Yani Triyani; Rika Nilapsari (UNISBA Press, 2023)
Abstract. COVID-19 is an infectious disease caused by the SARS-CoV-2 group. This disease has been declared by the WHO as a global pandemic. The first case of COVID-19 in Indonesia was reported on March 2, 2020, and the number has continued to increase until now. COVID-19 in Indonesia has spread to various regions, accompanied by increased cases and deaths. The severity of COVID-19 patients is classified into four, namely mild, moderate, severe, and critical, which can be determined by measuring the platelet-lymphocyte ratio value at routine hematological examinations. This RTL has become a new indicator of inflammation to determine the severity of COVID-19. Based on this phenomenon, the problem in this research is formulated as follows: (1) Is there a relationship between the platelet-lymphocyte ratio in moderate cases of COVID-19 at Al-Islam Hospital in Bandung? (2) Is there a relationship between the platelet-lymphocyte ratio in severe cases of COVID-19 at Al-Islam Hospital in Bandung? (3) Does the platelet-lymphocyte ratio act as an indicator of the severity of COVID-19 patients at Al-Islam Hospital Bandung? (4) What is the cut-off value of the platelet-lymphocyte ratio as an indicator of severity in COVID-19 patients at Al-Islam Hospital in Bandung?. The research design uses a diagnostic test method with a cross-sectional approach with data analysis techniques using Chi-square. The population selected in this study were confirmed COVID-19 patients based on RT-PCR results, which were treated at Bandung Al-Islam Hospital. Using the sampling technique, Total Sampling, the number of research samples was 350 patients. The data collection technique used in this study was from medical records. The data analysis technique used in this research is the descriptive analysis technique. The results of this study are: There is a relationship between the platelet-lymphocyte ratio (p-value=0.009) and the severity of COVID-19 patients at Al-Islam Hospital Bandung. Abstrak. COVID-19 merupakan penyakit menular yang disebabkan oleh kelompok SARS-CoV-2. Penyakit ini telah ditetapkan oleh WHO sebagai pandemi global. Kasus pertama COVID-19 di Indonesia dilaporkan pada tanggal 2 Maret 2020, dan jumlahnya terus meningkat hingga sekarang. Penyebaran COVID-19 di Indonesia menyebar ke berbagai wilayah dengan diiringi peningkatan jumlah kasus dan kematian. Derajat keparahan pasien COVID-19 diklasifikasikan menjadi empat yaitu derajat ringan, sedang, berat dan kritis yang dapat ditentukan dengan mengukur nilai rasio trombosit limfosit pada pemeriksaan hematologi rutin. RTL ini ini telah menjadi salah satu indikator peradangan yang baru untuk menentukan derajat keparahan COVID-19. Berdasarkan hal tersebut, maka permasalahan dalam penelitian ini dirumuskan sebagai berikut: (1) Apakah terdapat hubungan antara rasio trombosit limfosit pada kasus COVID-19 derajat sedang di RS Al-Islam Bandung? (2) Apakah terdapat hubungan antara rasio trombosit limfosit pada kasus COVID-19 derajat berat di RS Al-Islam Bandung? (3) Apakah rasio trombosit limfosit berperan sebagai indikator derajat keparahan pasien COVID-19 di RS Al-Islam Bandung? (4) Berapakah nilai cut off rasio trombosit limfosit sebagai indikator derajat keparahan pada pasien COVID-19 di RS Al-Islam Bandung?. Desain penelitian ini menggunakan metode uji diagnostik dengan pendekatan cross sectional dengan teknik analisis data menggunakan Chi-square. Populasi yang dipilih dalam penelitian ini adalah pasien terkonfirmasi COVID-19 berdasarkan hasil RT-PCR yang di rawat di Rumah Sakit Al-Islam Bandung. Dengan teknik pengambilan sampel yaitu Total Sampling diperoleh jumlah sampel penelitian sebanyak 350 pasien. Teknik pengumpulan data yang digunakan dalam penelitian ini adalah dari rekam medik. Adapun teknik analisis data yang digunakan dalam penelitian ini adalah teknik analisis deskriptif. Hasil penelitian ini adalah: Terdapat hubungan antara rasio trombosit limfosit (p-value=0,009) dengan derajat keparahan pasien COVID-19 di Rumah Sakit Al-Islam Bandung.